Critical Response Protocol: Supporting Preservice Science Teachers in Facilitating Inclusive Whole-Class Discussions - Ellingson, Charlene; Wieselmann, Dr. Jeanna; Dawn, Dr. Felicia (Innovations in Science Teacher Education, 2020)
Despite a large body of research on effective discussion in science classrooms, teachers continue to struggle to engage all students in such discussions. Whole-class discussions are particularly challenging to facilitate effectively and, therefore, often have a teacher-centered participation pattern. This article describes the Critical Response Protocol (CRP), a tool that disrupts teacher-centered discussion patterns in favor of a more student-centered structure that honors students’ science ideas. CRP originated in the arts community as a method for giving and receiving feedback to deepen critical dialog between artists and their audiences. In science classrooms, CRP can be used to elicit student ideas about scientific phenomena and invite wide participation while reducing the focus on “correct” responses. In this article, we describe our use of CRP with preservice science teachers. We first modeled the CRP process as it would be used with high school students in science classrooms, then discussed pedagogical considerations for implementing CRP within the preservice teachers’ classrooms. We conclude this article with a discussion of our insights about the opportunities and challenges of using CRP in science teacher education to support preservice teachers in leading effective whole-class discussion and attending to inclusive participation structures.